Unjust enrichment in Latvian Civil Law: insights from theory, court practice and the DCFR - Niedre, Elizabete Anna (Riga Graduate School of Law, 2022)
The concept of unjust enrichment has not been widely discussed and written about by legal scholars in the last twenty years, however, case law indicates that such disputes are common for both private individuals and businesses and there can be identified gaps in the current legal system. The present thesis explores the concept of unjust enrichment and its preconditions and limitations in Latvian Civil Law. The author critically analyses all types of reclaims of unjust enrichment in relation to their historical roots in Roman law and Latvian court practice. In Europe, a Draft Common Frame of Reference has been developed, with the seventh book focused on the regulation of unjust enrichment that is used as inspiration to develop ideas on how the legal system can be improved, as well as translation of the concept and other scenarios when unjust enrichment can occur. It is concluded that the Draft Common Frame of Reference can be a valuable source to improve Latvian Civil Law.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law; Unjust enrichment; Latvian Civil Law; Draft Common Frame of Reference